Некоторые вопросы систематики и распространения видов-двойников обыкновенной полевки на юге Европейской части Советского Союза - Гайченко, В.А.; Малыгин, В.М. (Вестник зоологии, 1975)
A geographic range, possible ways of settling and some other problems concerning the taxonomy of the species-M. arvalis Pall. doubles are considered on the basis of studies in the Microtus arvalis Pall karyotypes from the South of the European section of the USSR.